The genomics of postglacial vicariance and freshwater adaptations in European subarctic threespine sticklebacks - Adhikari, Dhurba; Karlsen, Bård Ove; Jørgensen, Tor Erik; Johansen, Steinar Daae; Nordeide, Jarle Tryti; Moum, Truls Borg (Frontiers in Ecology and Evolution, 2025)
Marine threespine sticklebacks (Gasterosteus aculeatus) have colonized numerous freshwater lakes since the last ice age. The loss of body armor, such as reduced pelvic spines and lateral plate numbers, is a recurrent feature upon freshwater colonization and is attributed to parallel evolution. This study examines genome-wide genetic diversity and differentiation among sticklebacks from a marine site and two freshwater lakes of the same watercourse in subarctic Europe. The upper lake is unique in that it harbors a population of polymorphic sticklebacks, some with fully developed and others with reduced pelvic structures. Our results based on deep sequencing of pooled population samples showed common signatures of selection for freshwater sticklebacks in certain parts of the genome, such as the Eda containing region, but also evidence of differential selection, and the presence of large chromosomal inversions that seem to play an essential role in stickleback evolution. Pelvic reduction in sticklebacks has previously been linked to deletions in the enhancers of the pituitary homeobox transcription factor gene (Pitx1). While the genetics of Pitx1 seem unable to fully explain pelvic spine polymorphism in this population, we found differentiation between spined and spineless sticklebacks in several genomic regions, which harbor genes that might be involved in pelvic development. Most significantly, genetic differentiation between spined and spineless sticklebacks was noted in a region of chromosome 9 where the gene Hand2, previously implicated in limb development, is located. Our findings suggest that pelvic reduction in these sticklebacks involves multiple genetic factors, indicating parallel evolution through polygenic influences.